Make headway for echinococcosis: Take along the ignored cases - Khan, Aisha; Ahmed, Haroon; Simsek, Sami (Tehran University of Medical Sciences (TUMS), 2019)
[Abstract Not Available]
Keywords: animal husbandry; Asia; disease burden; echinococcosis; endemic disease; epidemiological monitoring; human; hygiene; infection control; Letter; lifestyle and related phenomena; pathogen clearance; prevalence; risk factor; tropical disease; ultrasound